Cyanobacterial bloom mitigation by sanguinarine and its effects on aquatic microbial community structure. (October 2019) - Lin, Yiqing; Chen, Anwei; Luo, Si; Kuang, Xiaolin; Li, Renhui; Lepo, Joe Eugene; Gu, Ji-Dong; Zeng, Qingru; Shao, Jihai
Abstract: Sanguinarine has strong inhibitory effects against the cyanobacterium Microcystis aeruginosa . However, previous studies were mainly limited to laboratory tests. The efficacy of sanguinarine for mitigation of cyanobacterial blooms under field conditions, and its effects on aquatic microbial community structure remain unknown. To elucidate these issues, we carried out in situ cyanobacterial bloom mitigation tests. Our results showed that sanguinarine decreased population densities of the harmful cyanobacteria Microcystis and Anabaena . The inhibitory effects of sanguinarine on these cyanobacteria lasted 17 days, after which the harmful cyanobacteria recovered and again became the dominant species. Concentrations of microcystins in the sanguinarine treatments were lower than those of the untreated control except during the early stage of the field test. The results of community DNA pyrosequencing showed that sanguinarine decreased the relative abundance of the prokaryotic microorganisms Cyanobacteria, Actinobacteria, Planctomycetes and eukaryotic microorganisms of Cryptophyta, but increased the abundance of the prokaryotic phylum Proteobacteria and eukaryotic microorganisms within Ciliophora and Choanozoa . The shifting of prokaryotic microbial community in water column was directly related to the toxicity of sanguinarine, whereas eukaryotic microbial community structure was influenced by factors other than direct toxicity. Harmful cyanobacteria mitigation efficacy and microbial ecological effects of sanguinarine presented in this study will inform the broad application of sanguinarine in cyanobacteria mitigation. Graphical abstract: Image 1 Highlights: Sanguinarine effectively decreases the cell density of harmful cyanobacteria. Sanguinarine treatment decreases microcystins concentration in water column. Sanguinarine treatment improves water quality. Prokaryotic community shifting is different from that of eukaryotic microbes.